2018
DOI: 10.1088/1361-6641/aace43
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of selective dry and wet etching of germanium–tin (Ge1−xSnx) on germanium

Abstract: A comparative study of selective dry and wet etching methods for germanium-tin (Ge 1−x Sn x ) alloys (3.5% < x < 7.7%) and germanium (Ge) is carried out. Both etching methods are optimized from the perspectives of selectivity and morphology, and then compared. A special behavior of the selective dry etching process is discovered and explained, whereby the selectivity has a dramatic increase to as high as 336 when the Sn concentration is above 6%. Different morphologies of suspended microstructures fabricated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The similar line tendency indicates that the etch rate of Ge is roughly equal for Ge 0.902 Sn 0.098 disks with different diameters of 3 μm and 5 μm, and is in agreement with the value of the etch rate from Ref. [30]. Moreover, the minimum diameter of Ge pedestal for standing GeSn microdisk is about 300 nm.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The similar line tendency indicates that the etch rate of Ge is roughly equal for Ge 0.902 Sn 0.098 disks with different diameters of 3 μm and 5 μm, and is in agreement with the value of the etch rate from Ref. [30]. Moreover, the minimum diameter of Ge pedestal for standing GeSn microdisk is about 300 nm.…”
Section: Resultssupporting
confidence: 89%
“…It will reduce the wet etching rate of GeSn and lead to a higher etch selectivity of Ge over GeSn. The previous study has reported that the H 2 O 2 based wet etch (H 2 O 2 :NH 4 OH: H 2 O = 2:0.5:80), the same with this work, achieves an etch selectivity of Ge over Ge 0.928 Sn 0.072 of 9:1 [30]. Figure 3a shows the cross-sectional TEM micrograph of the 5 μm diameter GeSn circular mesa without the top polysilicon layer.…”
Section: Gesn Growth and Microdisk Fabricationsupporting
confidence: 71%
See 3 more Smart Citations